(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the effectiveness of psychological support education in reducing anxiety among students at the University of Medicine and Pharmacy, Ho Chi Minh City, who exhibit anxiety disorders based on the Zung Self-Rating Anxiety Scale after a four-week intervention. Subjects and Methods: A pre-post study was conducted on 30 students at the University of Medicine and Pharmacy, Ho Chi Minh City, who exhibited anxiety disorders. These students participated in psychological support education, consisting of four sessions over four weeks, facilitated by a psychologist. Anxiety levels were assessed using the Zung Self-Rating Anxiety Scale (SAS), and mental health status was evaluated using the SF-36 Quality of Life Scale before and after the intervention. Results: After four weeks of psychological support education, anxiety scores significantly decreased, while mental health scores significantly increased compared to pre-intervention levels. Conclusion: Psychological support education significantly reduces anxiety and markedly improves mental health, with statistically significant results.